SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK DENGAN METODE SMART BERBASIS WEB (STUDI KASUS TELKOM JOMBANG) - Solikhan; Setyo Permadi , Ginanjar; Fatkhur Rizal , Muhammad (Inovate, 2023)
PT. Telkom Jombang is still carried out with subjective perceptions by the team leader only, so that the assessment given is still not inaccurate. This can cause an injustice to the results of the best employee decisions. The Decision Support System method used in this study is the. The author chose this method because it has several advantages compared to other decision-making methods, one of which is being able to add/subtract alternatives The system can automatically provide ranking results so that it does not require manual calculations and allows the selection process to be carried out quickly, precisely and accurately. In several system tests carried out by the system, there was an error. From some of these tests, it can be taken that the system accuracy comparison value is 90%. Keywords: Employee,The SMART, Decision Support System